INTEGRASI KONTEN LOKAL DALAM KURIKULUM PENDIDIKAN AGAMA ISLAM: DINAMIKA, TANTANGAN, DAN PELUANG DI ERA KONTEMPORER - Hironimus Dapa; Anugrah Giffari; Ishomuddin (Almarhalah: Jurnal Pendidikan Islam, 2026)
The development of a local content-based curriculum for Islamic Religious Education (PAI) has become a crucial discourse in educational reform. This article analyzes the evolution, dynamics, and implications of integrating local content into the PAI curriculum through a systematic literature review. Findings indicate that the integration of local wisdom, supported by policies like the Kurikulum Merdeka (Emancipated Curriculum), significantly enhances educational relevance, student engagement, and character formation. Modern PAI curricula are also beginning to respond to contemporary issues such as social cohesion through multicultural education, environmental awareness, and digital literacy grounded in Islamic values. Despite these advancements, educators face significant challenges, including resource limitations, training needs, and the complexities of assessment. This article concludes that the success of this curriculum localization hinges on collaborative synergy among policymakers, educators, and the community. Furthermore, innovative teaching approaches are essential to shape students with robust identities, rooted in local culture, yet prepared to meet global challenges.